2020
DOI: 10.1148/radiol.2020202352
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Barotrauma in Patients with COVID-19 on Invasive Mechanical Ventilation

Abstract: A t New York University Langone Health at the height of the coronavirus disease 2019 (COVID-19) pandemic, 22% of hospitalized patients diagnosed with COVID-19 infection required invasive mechanical ventilation (IMV) (1). We noted many patients with COVID-19 infection who developed pneumothorax, pneumomediastinum, and pneumopericardium, and in some cases, at multiple separate time points. Given this observation, we hypothesized that barotrauma related to IMV was elevated in patients with COVID-19 infection. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
315
5
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(364 citation statements)
references
References 25 publications
23
315
5
21
Order By: Relevance
“…This is in agreement with a previously published study on more than 5000 mechanically ventilated patients, in which the presence of air outside the tracheobronchial tree (pneumothorax, pneumomediastinum, subcutaneous emphysema) was unrelated to airway pressures and tidal volume [11]. Therefore, the automatic association between barotrauma and presence of air outside the tracheobronchial tree in mechanically ventilated patients [11,12] should be reconsidered. Actually, the term "barotrauma" should be used in presence of air outside the tracheobronchial tree only when concurrent with elevated airway pressure.…”
Section: Pneumomediastinum/subcutaneous Emphysemasupporting
confidence: 90%
“…This is in agreement with a previously published study on more than 5000 mechanically ventilated patients, in which the presence of air outside the tracheobronchial tree (pneumothorax, pneumomediastinum, subcutaneous emphysema) was unrelated to airway pressures and tidal volume [11]. Therefore, the automatic association between barotrauma and presence of air outside the tracheobronchial tree in mechanically ventilated patients [11,12] should be reconsidered. Actually, the term "barotrauma" should be used in presence of air outside the tracheobronchial tree only when concurrent with elevated airway pressure.…”
Section: Pneumomediastinum/subcutaneous Emphysemasupporting
confidence: 90%
“…For instance, cavitating lung lesions can manifest in patients with COVID-19 (Fig 6), which may be due to mechanical ventilator-induced lung injury. Of interest, authors of a study (52) reported that barotrauma (pneumothorax, pneumomediastinum) occurs in approximately 15% of patients with COVID-19 who require invasive mechanical ventilation, and that it is more likely to occur in younger patients. Pericardial effusion may be seen as a complication in the setting of cardiac injury.…”
Section: Chest Ct Abnormalities With Low Incidence (<10%)mentioning
confidence: 99%
“…MyGuinness et al reported a rate of barotrauma of 15% in a mixed collective of invasive ventilated COVID-19 patients. 4 However, this publication mainly focused on radiological findings and did not investigate a possible association between barotrauma and respirator settings.…”
Section: Discussionmentioning
confidence: 99%